2014
DOI: 10.1186/1471-2156-15-10
|View full text |Cite
|
Sign up to set email alerts
|

Proliferator-activated receptor gamma Pro12Ala interacts with the insulin receptor substrate 1 Gly972Arg and increase the risk of insulin resistance and diabetes in the mixed ancestry population from South Africa

Abstract: Background: The peroxisome proliferator-activated receptor gamma (PPARG), Pro12Ala and the insulin receptor substrate (IRS1), Gly972Arg confer opposite effects on insulin resistance and type 2 diabetes mellitus (T2DM). We investigated the independent and joint effects of PPARG Pro12Ala and IRS1 Gly972Arg on markers of insulin resistance and T2DM in an African population with elevated risk of T2DM. In all 787 (176 men) mixed-ancestry adults from the Bellville-South community in Cape Town were genotyped for PPAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 48 publications
2
20
1
1
Order By: Relevance
“…However, in the present study we did not find any significant association between ENPP1 SNPs and indicators of insulin resistance/sensitivity. Instead, in a previous study we demonstrated that the PPARGPro12 allele was associated with insulin resistance in this mixed ancestry cohort 21 . Like ENPP1, PPARG plays a role in insulin sensitivity.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…However, in the present study we did not find any significant association between ENPP1 SNPs and indicators of insulin resistance/sensitivity. Instead, in a previous study we demonstrated that the PPARGPro12 allele was associated with insulin resistance in this mixed ancestry cohort 21 . Like ENPP1, PPARG plays a role in insulin sensitivity.…”
Section: Discussioncontrasting
confidence: 59%
“…Although few number of T2DM susceptibility genes discovered through candidate gene, linkage analyses, and GWA studies elsewhere have been replicated in African studies [16][17][18][19][20][21] , it must also be emphasized that many other association studies failed to show significant and replicable findings [22][23][24] . Therefore in this study we investigated three genes, namely, TCF7L2, FTO, and ENPP1 as risk factors for T2DM in a South African ethnic population group of Mixed-ancestry (Coloureds) with a unique genetic architecture.…”
Section: Introductionmentioning
confidence: 99%
“…Al-Safar et al [20] also suggested that confirmed that Pro12Ala mutation in PPARG2 is not associated with T2DM risk in this population. In a study for South Africa population, Vergotine et al [21] reported that the Pro12Ala of PPARG2 is significantly associated with insulin resistance and this polymorphism interacts with IRS1 Gly972Arg, to increase the risk of T2DM. Hahn et al [22] indicated that our data confirm a beneficial effect of the PPARG1 12Ala allele on insulin resistance and glucose metabolism in PCOS women.…”
Section: Discussionmentioning
confidence: 99%
“…Among several genetic variants of the PPARγ2 gene, two polymorphisms; Pro12Ala of the exon B (rs1801282) and the C1431T silent substitution (rs3856806) in the exon 6, are the most frequently occurring SNPs and have been associated with various diseases [13][14][15][16][17][18][19][20][21]. The association of Pro12Ala polymorphism with T2D, insulin resistance, obesity and metabolic disorders has been reported in several studies [24][25][26]. The C1431T polymorphism has also been studied in relation to obesity, diabetes and coronary heart disease [18,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%